Dietary restriction in cerebral bioenergetics and redox state() - Amigo, Ignacio (Elsevier, 2014)
The brain has a central role in the regulation of energy stability of the organism. It is the organ with the highest energetic demands, the most susceptible to energy deficits, and is responsible for coordinating behavioral and physiological responses related to food foraging and intake. Dietary interventions have been shown to be a very effective means to extend lifespan and delay the appearance of age-related pathological conditions, notably those associated with brain functional decline. The present review focuses on the effects of these interventions on brain metabolism and cerebral redox state, and summarizes the current literature dealing with dietary interventions on brain pathology.